Early regional cuprizone‐induced demyelination in a rat model revealed with MRI. (22nd May 2017) - Oakden, Wendy; Bock, Nicholas A.; Al‐Ebraheem, Alia; Farquharson, Michael J.; Stanisz, Greg J.
Abstract : The cuprizone model of demyelination is well established in the mouse as a tool for the study of the mechanisms of both demyelination and remyelination. It is often desirable, however, to have a larger model, such as the rat, especially for imaging‐based studies, yet initial work has failed to show demyelination in cuprizone‐fed rats. Several recent studies have demonstrated demyelination in the rat, but only in the corpus callosum. In this study, we acquired high‐resolution, three‐dimensional images of the whole brain every 2 weeks, using a T 1 ‐weighted magnetization‐prepared rapid acquisition gradient echo imaging sequence, optimized for myelin contrast, in order to assess myelination across the entire rat brain over a period of 8 weeks on a 1% cuprizone diet. We observed a consistent pattern of demyelination, beginning in the cerebellum by 4 weeks and involving more rostral regions of the brain by 8 weeks on the cuprizone diet, with validation using Luxol fast blue histology. This imaging technique permits the effects of cuprizone‐induced demyelination to be followed longitudinally in a single animal, over the entire brain. In turn, this may facilitate the establishment of the cuprizone model of demyelination in the rat. Abstract : Demyelination was observed in rat brain following a 1% cuprizone diet, using a high‐resolution, three‐dimensional, T 1 ‐weighted, magnetization‐prepared rapid acquisition gradient echo imaging protocol optimized for myelin contrast. Demyelination followed a specific pattern, beginning in the cerebellar nuclei by 4 weeks and involving more rostral regions of the brain by 8 weeks. This imaging technique permits the effects of cuprizone‐induced demyelination to be followed longitudinally in a single animal over the entire brain.